Pengaruh Social Influence Perceived Usefulness Terhadap Interest In Using Aplikasi Mobile Wallet Flip Melalui Mediasi Attitude Towards - Vania Aureli Nurizky; Tirton Nefianto (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
In the ever-evolving digital age, mobile wallet apps have become an integral part of everyday life. This kind of application provides an efficient and secure way to conduct financial transactions via mobile devices. The purpose of this study was to determine the effect between Social Influence, Perceived Usefulness on individual interest in using the Flip mobile wallet application which is mediated by Attitude Towards (attitude role) then to determine the most dominant variable in influencing interest, namely the use of the Flip mobile wallet application. The sample in this study amounted to 145 respondents using data collection techniques using purposive sampling. The data is then processed using the Structural Equation Model (SEM) method with SmartPLS software. based on the test results it is known that Social Influence has no effect on Attitude Towards while Perceived Usefulness has a positive effect, then Social Influence has no effect on Interest in Using while Perceived Usefulness has a positive effect. Attitude Towards has no effect on Interest in Using. Furthermore, the mediating role of Attitude Towards cannot have an effect in mediating Social Influence on Interest in Using and Perceived Usefulness on Interest in Using.